2002
DOI: 10.1046/j.1464-410x.2002.02969.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and progression in stage T1G3 bladder tumour with intravesical bacille Calmette‐Guérin (Danish 1331 strain)

Abstract: This series further confirms the benefits of intravesical BCG (Danish 1331) in an adjuvant setting; furthermore, this treatment facilitates bladder preservation by reducing recurrences and delaying the progression in many patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Adjuvant intravesical immunotherapy with the attenuated tuberculosis vaccine BCG has proven to be effective and has become the standard adjuvant treatment for these patients [22] and a useful modality in delaying cystectomy. In a recent meta-analysis, it was clearly shown that treatment with intravesical BCG decreases tumor recurrence and progression but no effect on patient survival was documented [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant intravesical immunotherapy with the attenuated tuberculosis vaccine BCG has proven to be effective and has become the standard adjuvant treatment for these patients [22] and a useful modality in delaying cystectomy. In a recent meta-analysis, it was clearly shown that treatment with intravesical BCG decreases tumor recurrence and progression but no effect on patient survival was documented [23]. …”
Section: Discussionmentioning
confidence: 99%
“…In superfi cial tumors (Ta, T1), the net benefi t of BCG therapy appears to be an increase in the recurrence-free interval and a delay in cystectomy. Thus, it is possible to preserve the bladder in up to 88% of patients after BCG therapy [9] . T1G3 tumors treated by TUR alone had a recurrence rate of 50-80% and progressed in 25-50% of the cases [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Nine of these patients had muscle-invasive disease and 1 patient (multilocular stage pT1, grade 3) had radical cystectomy after a 24-month followup. After a second course of BCG 1 patient, who was not (24) disease-free (39) pT1G1 ( 27) pT1G1 (36) disease-free (48) pT1G1 multiple (15) pT1G2 (30) disease-free (54) pT1G1 multiple (9) TUR-BT pT1G1 (24) (18) pT1G2 (21) pT2G3 (30) cystectomy disease-free (38) pT1G2 multiple (12) pT1G3 (27) TUR-BT+BCG pT3aG3 node+(36) cystectomy + chemotherapy alive with metastases (50) pT1G3 (15) died, other cause (33) pT1G3 (9) pT2G3 (21) After BCG instillation, signifi cant side effects were seen in 10 (20.4%) of 49 patients, including gross hematuria in 2 (4.1%), severe irritative voiding symptoms in 7 (14.3%), and decreased bladder capacity in 1 (2%).…”
Section: Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravesical instillations of BCG have become the first-line treatment of such tumours. The most recent reports dealing with the results of BCG therapy in patients with T1G3 tumour are listed in Table 2 [3,[5][6][7][8][9]. These studies have reached very heterogeneous conclusions.…”
Section: Discussionmentioning
confidence: 99%